On symmetries of crystals with defects related to a class of solvable groups (S2) - Parry, Gareth P.; Nicks, Rachel (Wiley, 2012)
We find the geometrical symmetries of discrete structures which generalize the perfect lattices of crystallography to account for the existence of continuous distributions of defects.